2011
DOI: 10.5539/ass.v7n7p102
|View full text |Cite
|
Sign up to set email alerts
|

Key Performance Indicators (KPIs) in the Public Sector: A Study in Malaysia

Abstract: Several years ago Key Performance Indicators (KPIs) becoming a best measurement practiced by the government sectors. By practicing this approach in government agencies, the failure of delivery system which always voice out the public will address accordingly. Thus, this paper aims to look at the implementation of KPIs) mainly in Malaysian public sectors in response with Government Circular 20. With some adjustment of reformation in the public sector, the government has developed their own set of KPIs to measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 1 publication
0
15
0
2
Order By: Relevance
“…In addition, the use of KPIs also contributed to several improvements in their administration and service delivery towards public at large [11]. However, the authors noted in their research paper that their study was based on archival data, and thus it provides limited insight into how managers perceived relevance and usefulness of KPIs in measuring their performance (pp.103).…”
Section: The Attitude Of Managers Towards Kpismentioning
confidence: 65%
See 3 more Smart Citations
“…In addition, the use of KPIs also contributed to several improvements in their administration and service delivery towards public at large [11]. However, the authors noted in their research paper that their study was based on archival data, and thus it provides limited insight into how managers perceived relevance and usefulness of KPIs in measuring their performance (pp.103).…”
Section: The Attitude Of Managers Towards Kpismentioning
confidence: 65%
“…In another study done by [11] with the aim to look at the implementation of KPIs in response to Government Circular 20, the authors found that the use of KPIs in government agencies has been successful in measuring organizational as well as individual performance. In addition, the use of KPIs also contributed to several improvements in their administration and service delivery towards public at large [11].…”
Section: The Attitude Of Managers Towards Kpismentioning
confidence: 99%
See 2 more Smart Citations
“…One of the methods is the use of Key Performance Indicators (KPI) to measure the organisation and practitioners for cooperation and efficiency even though gaps between theory and practice have been reported (Zakaria et al 2011;Patrizia et al 2005). The MOP and MOEP will be necessary to evaluate the whole system.…”
Section: Operation Strategy Performance and Measurementmentioning
confidence: 99%